2009
DOI: 10.1007/s00497-008-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sheltered load on reproduction in Solanum carolinense, a species with variable self-incompatibility

Abstract: In previous studies, we have investigated the strength of self-incompatibility (SI) in Solanum carolinense, a highly successful weed with a fully functional SI system that inhabits early successional and other disturbed habitats. We have found that the SI response in S. carolinense is a plastic trait-its strength being affected by the age of the flowers, and the presence of developing fruits and that there are genetic differences among families in their self-fertility. However, in species with a fully function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
4
12
1
Order By: Relevance
“…Furthermore, we showed segregation bias against S15 in offspring from both self and incompatible crosses (Table 1). Our study in SSI corroborates with the results obtained in GSI in S. carolinense (i) by Stone (2004), who found a sheltered load associated to two alleles at the S locus, and (ii) by Mena-Ali et al (2009), who showed some variations in the strength of the sheltered load carried by different S alleles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we showed segregation bias against S15 in offspring from both self and incompatible crosses (Table 1). Our study in SSI corroborates with the results obtained in GSI in S. carolinense (i) by Stone (2004), who found a sheltered load associated to two alleles at the S locus, and (ii) by Mena-Ali et al (2009), who showed some variations in the strength of the sheltered load carried by different S alleles.…”
Section: Discussionsupporting
confidence: 92%
“…Other stages that have a great importance for the fitness of the progeny like number of flowers and male and female fertility could also be affected by the effect of the sheltered load and require further study. Mena-Ali et al (2009) indeed showed that sheltered load may have an effect on the number of flowers and on the seed set in S. carolinense, a species with GSI.…”
Section: Discussionmentioning
confidence: 90%
“…Overall, our results add to the growing body of evidence that alleles at a locus under balancing selection can build up a deleterious load (Stone, 2004;Llaurens et al, 2009b;Mena-Ali et al, 2009), as predicted by theory (Uyenoyama, 2005;van Oosterhout, 2009). As all studies so far, we found evidence for such a load for some, but not all alleles.…”
Section: Genetic Load Attributable To the S-locussupporting
confidence: 82%
“…In addition, S-locus homozygotes were underrepresented in the viable progeny. A similar study in the same species found the opposite-that S-locus homozygotes were over-represented in selfed progeny-but revealed that homozygotes had reduced fitness in terms of growth (Mena-Ali et al, 2009). Both studies suggested that different S-alleles were associated with a different genetic load, depending on the evolutionary time for mutations to accumulate, or due to different purging histories.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation